2015
DOI: 10.1063/1.4913600
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and spectral phonon properties of freestanding and supported silicene

Abstract: We conduct molecular dynamics (MD) simulations to study the thermal conductivity of freestanding silicene and silicene supported on an amorphous silicon dioxide (SiO2) substrate in the temperature range from 300 to 900 K. The results show that the thermal conductivity decreases with increasing temperature and that the presence of the SiO2 substrate results in a great reduction, up to 78% at 300 K, to the thermal conductivity of silicene. With atomic trajectories from equilibrium MD simulations, we perform spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 58 publications
12
54
0
Order By: Relevance
“…For instance, the thermal conductivity of ASNT and ZSNT decreases by about 50% when the temperature increases from 300-550 K while it decreases 18% in the temperature growth from 550-700 K. We notice that the thermal conductivity of silicene nanotubes versus temperature is not sensitive to chirality thus the MD results obtained for ASNT and ZSNT are the same. Our findings are in agreement with previously research reported on the temperature dependence of the thermal conductivity of bulk silicene and silicene nanosheets [47,49]. Studying the thermal properties of silicene nanotubes under extreme condition such as defects and strain is essential for practical applications.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For instance, the thermal conductivity of ASNT and ZSNT decreases by about 50% when the temperature increases from 300-550 K while it decreases 18% in the temperature growth from 550-700 K. We notice that the thermal conductivity of silicene nanotubes versus temperature is not sensitive to chirality thus the MD results obtained for ASNT and ZSNT are the same. Our findings are in agreement with previously research reported on the temperature dependence of the thermal conductivity of bulk silicene and silicene nanosheets [47,49]. Studying the thermal properties of silicene nanotubes under extreme condition such as defects and strain is essential for practical applications.…”
Section: Resultssupporting
confidence: 93%
“…In semimetals, such as silicene, the contribution of electrons on the thermal conductivity at room temperature and above is less than that of phonons. Therefore, non-equilibrium molecular dynamics (NEMD) simulation that ignores electron transport can be used to investigate the thermal properties of silicene [47]. In this research, the non-equilibrium molecular dynamics (NEMD) simulation is carried out using Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) [48] to study the effect of the grain boundary, axial strain, random vacancy defect, and temperature on the thermal conductivity of silicene nanotubes.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…Unlike graphene in which all carbon atoms form honey-cone structures within a flat plane, silicon atoms in silicone show a buckled structure, resulting in unique thermal transports fundamentally differing from that in other 2D materials, namely (a) longitudinal and transverse acoustic phonons dominate the thermal transports and the acoustic out-of-plane phonon modes only have less than 10% contributions to the total thermal conductivity [114][115][116][117]; (b) thermal conductivity increases dramatically with tensile strain due to enhancement in acoustic phonon lifetime [118][119][120]. Unfortunately, no experiment on thermal conductivity in silicene has been reported.…”
Section: Silicenementioning
confidence: 99%
“…Wang et al, 13 Li et al 5 and Hu et al 2 employed the Tersoff potential to investigate the thermal conductivity of free-standing and supported single layer silicene. Tersoff potential 12 has been widely used to describe the Si atom interactions in bulk silicon and silicon nanotubes.…”
mentioning
confidence: 99%